Moto and me : my year as a wildcat's foster mom - Eszterhas, Suzi (Owlkids Books, 2017)
"This is the story of Suzi and her personal rescue and rehabilitation of an orphaned serval cat named Moto. Ultimately, Moto was able to return to the wild because of Suzi's dedication to being the best foster mom she could be - and it wasn't easy! She was camping alone in the bush in Kenya, with very little contact with the outside world. Someone came to her with an orphaned serval cat because they knew she'd be willing and want to help - nobody knew what else to do. Determined to nurse the kitten back to health and help him learn, grow, and return to the wild, Suzi did everything she could think of to be the best serval mom she could be. She had a little bit of help from a couple other people who had some experience with orphaned wild animals, but for the most part, it was just her and Moto out there, figuring things out based on Suzi's experience observing animal rescues and her instincts about the animal's needs."--